2000
DOI: 10.1139/v99-249
|View full text |Cite
|
Sign up to set email alerts
|

The one- and two-photon photochemistry of benzylsilacyclobutanes, acyclic benzylsilanes, and 1,1,2-triphenylsilacyclobutane

Abstract: The photochemistry of several α-silylbenzyl compounds has been investigated in hexane and in methanol solution. Direct photolysis of 1-benzyl-1-methylsilacyclobutane (1) in methanolic hexane solution produces 1-propyl-1-methyl-2,3-benzosilacyclobutene (6) in quantitative yield, by a sequential two-photon process involving the photoactive isotoluene derivative 1-methylene-6-(1-methylsilacyclobutyl)-2,4-cyclohexadiene (13a), which has been identified on the basis of its 1H NMR and UV absorption spectra. In contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…We suspect, but cannot yet confirm (vide infra), that these transients are related to the phototransposition chemistry, as we have not observed behavior of this type in any of the arylsilacyclobutane derivatives whose photochemistry we have studied previously. 11,[17][18][19] The phototransposition of substituted benzene derivatives is thought to proceed via excited singlet state isomerization to a benzvalene derivative, which is then transformed into the aromatic isomer via tripletsensitized (quantum chain) decomposition. 13 In the case of 6c, as with any unsymmetrically disubstituted benzene derivative, the initial isomerization can in principle lead to six distinct benzvalene isomers, of which two (9c and 10c in eq 4) would yield 8c upon triplet-sensitized decomposition; the other four leave the ortho-substituent unchanged from its initial position.…”
Section: Discussionmentioning
confidence: 99%
“…We suspect, but cannot yet confirm (vide infra), that these transients are related to the phototransposition chemistry, as we have not observed behavior of this type in any of the arylsilacyclobutane derivatives whose photochemistry we have studied previously. 11,[17][18][19] The phototransposition of substituted benzene derivatives is thought to proceed via excited singlet state isomerization to a benzvalene derivative, which is then transformed into the aromatic isomer via tripletsensitized (quantum chain) decomposition. 13 In the case of 6c, as with any unsymmetrically disubstituted benzene derivative, the initial isomerization can in principle lead to six distinct benzvalene isomers, of which two (9c and 10c in eq 4) would yield 8c upon triplet-sensitized decomposition; the other four leave the ortho-substituent unchanged from its initial position.…”
Section: Discussionmentioning
confidence: 99%
“…This species is proposed to undergo competing loss of ethylene to yield silene 2 and migration of the methoxy group from the benzylic carbon to silicon, the driving force for which is the formation of the relatively strong Si-O bond in the product proposed to be a secondary photolysis product, while dialkoxysilane 7 is the product expected from (dark) reaction of 8 with methanol. 9 The considerably lower yield of 6 in the photolysis of 1 in methanol (compared to that in hexane) is consistent with a lower pseudophotostationary state concentration of 8 due to its reaction with the solvent to form 7. Additional evidence that 6 is formed via secondary photolysis of 8 was obtained by photolyzing a hexane solution of 1 simultaneously with 254 and 350 nm light sources.…”
mentioning
confidence: 78%
“…The UV and NMR spectra of 8, its lifetime, and photochemical and ground-state reactivities are analogous to those of other 1-methylene-6-silyl-2,4-cyclohexadiene derivatives that have been reported. 9 The rearrangement of 9 to 10 can be viewed as an intramolecular homolytic substitution resulting from attack of the silicon radical center at oxygen. While we are unaware of any precedent for this process in silicon (mono)radical chemistry, preliminary DFT calculations indicate that the analogous rearrangement of a silyl radical closely related to 9 is exothermic by ca.…”
mentioning
confidence: 99%
“…In numerous papers it has been shown that the thermolysis or flash photolosis of silacyclobutanes leads to either intermediate or stable divalent silicon compounds like silenes R 2 Si@C and silylenes R 2 Si: [8][9][10][11][12][13][14][15]. Silacyclobutanes have been recently utilized as carbanion pump in anionic living polymerization for the synthesis of block copolymers [16,17].…”
Section: Introductionmentioning
confidence: 99%